(untitled) (Andamios, Revista de Investigación Social, 2004)
The inhabitants of a city with the dimensions and characteristics of a metropoli like Mexico City’s, build a chain of images around their environment around the meaning of living the city and what is urban. A cultural atmosphere called modernization produces the construction of these representations. Living in such a cultural atmosphere implies a determined way of being and acting in specific contexts. In a city of millions where many cities and differentiated urban groups coexist, it turns out necessary to consider carefully the ways of solving the contradiction between totalizing visions and particular ways of un- derstanding the city.